Identification of Tadris Biology Students Level Understanding and Misconceptions on the Material of Quantities and Units Using 3-Tier Diagnostic Method - Meiliyadi, Lalu Ahmad Didik; Asyari, Akhmad; Arizona, Kurniawan (Jurnal Penelitian Pendidikan IPA, 2023)
The level of understanding and misconceptions of Tadris Biology students at Mataram State Islamic University has been analyzed. The tested sub-materials, including quantities, units, and measurements, are adjusted to the Student Semester Learning Plan in the Basic Physics Course. The method used was observation using the 3-tier Diagnostic Test. The 3-tier Diagnostic Test is a question consisting of multiple choice questions accompanied by statements of reasoning and confidence levels.. This method has three stages of student answers: concept answers, reasons, and confidence levels. Based on the results of diagnostic tests on students, it was obtained that the level of complete understanding of students was 23.53%, and the level of misconceptions was 23.53%. The level of misconception is 23.53%. Students experienced the greatest misconceptions in the physical quantities sub-material, which amounted to 52.94%, and the lowest in the measurement material at 5.89%. Most students believe that the angle is not a principal quantity, as indicated by the wrong student answers accompanied by the reasons and with a high confidence level-certainly a misconception because according to experts, the angle is also a principal quantity. Although the percentage of misconceptions is tiny, students still experience misconceptions in each submitter.